Injury prevention in handball - Luig, P.; Henke, T. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
Literature search identified 109 recommendations in four key categories related to preventing handball injuries. An expert panel (n=11) assessed the value of these 109 recommendations to expose the most promising ones, which were then pilot tested in two national federations. As a result of this process general recommendations on how to prevent handball injuries are given. Moreover, smart ways of promoting injury prevention in the handball community are depicted.